Enactment of the Organizational Cost Structure in Value Chain Configuration: A Contribution to Strategic Cost Management - Carsten Scheibye (Copenhagen Business School (CBS), 2015)
This PhD Thesis researches into Strategic Cost Management with a general research interest in, how top management makes sense about the organization's cost structure in strategic decisions about the configuration of the value chain. The empirical setting is among other confined by organizations' outsourcing and relocation ventures, where `cost reduction' is a prominent argument behind the decisions. The overall research purpose is to develop explanatory propositions about, how Strategic Cost Management practices might be `enacted and given meaning' (Baxter and Chua, 2003, p. 112) by top management. Such understanding is suggestable of scholarly interest. It is well-known to academia that extant contributions from the literary realms of Supply Chain Management and Management Accounting irradiate that decisions to reconfigure the organizations' value chains can encompass substantial investments and embed pivotal organizational tradeoffs. Thus, it is of centrality in relation to the organizations' competitive positions. Secondly, contemporary contributions within Supply Chain Management or in close juxtaposition hereto increasingly question decision making schemes based on `pure cost efficiency considerations' (e.g. Kinkel, 2012, p. 696). These contributions progressively advocate for a broader view upon organizations' approaches to value chain configuration. This perspective on cost management within the realm of the value chain is shared by Management Accounting researchers (e.g. Anderson, 2007; Anderson and Dekker, 2009ab). These Management Accounting situated researchers, thirdly, direct attention to a disproportionate research emphasis on cost management issues with a focal point of that of improving cost performance given a certain strategy and cost structure, i.e. executional cost management, opposed to research into the cost structural choices associated with the design of the value chain, i.e. structural cost management (e.g. Anderson and Dekker, 2009ab). This is perhaps surprising, when the centrality of the cost structural choices in relation to the competitive position is considered. These scholars do, fourthly, stress the amble opportunity to understand the more `complex economic and social forces' (Anderson, 2007, p. 483) that govern the management of the structural costs.
hdl:10398/9242
Keywords: 650